Malaysian islamic banks’ efficiency: an intra-bank comparative analysis of islamic windows and full-fledged subsidiaries - Salami, Oladipupo Luqman; Adewale, Abideen Adeyemi (Universiti Malaysia Sarawak, 2015)
This paper aims to fill an apparent dearth of empirical studies that compare the efficiency of Islamic banks in Malaysia during their operation as Islamic windows and later transformation to full-fledged Islamic banks. Data obtained from the annual financial reports of the sampled banks is analyzed using the Data Envelopment Analysis (DEA) via DEAP 2.1 software to assess both the technical and scale efficiency of the banks under sample. Results obtained indicate that the banks have improved over the years in terms of both scale and technical efficiency although the former takes prominence. In general, the banks were found to be more efficient as Islamic windows compared to being full-fledged subsidiaries. This augurs well for the current disposition where, as per the Islamic Financial Service Act 2013, Islamic banks in Malaysia may now operate as full-fledged banks from their hitherto Islamic banking window status.